Angiotensin converting enzyme inhibitor-induced penile angioedema: A case report - Anthony Acosta; Enas Alamreia; Nimra Afreen; Zane Elfessi (JEM Reports)
Background: Angioedema is local swelling in the subcutaneous or submucosal layers resulting from bradykinin-mediated capillary leakage allowing fluid to accumulating in the interstitial space. It is estimated to affect up to 1 in 10,000 individuals each year worldwide. Case report: Angioedema typically affects areas such as the face, lips, mouth, and throat, larynx, uvula, and GI tract, but rarely affects the genitals. Causes of angioedema include allergic reactions, drug-induced, hereditary factors, acquired factors, and idiopathic. We report a rare case of penile angioedema due to the angiotensin-converting enzyme (ACE) inhibitor lisinopril.Why should an EM Physician be aware of this?Penile angioedema is an extremely rare complication of ACE inhibitor use and should be included in the differential diagnosis for genital swelling. In the absence of complications from angioedema, such as paraphimosis, patients can be discharged from the emergency department without the need for pharmacotherapy as the swelling is self-resolving after discontinuation of the offending agent.